Safety and Efficacy of NC120 for Improving Lipid Profile: A Double Blind Randomized Controlled Trial - Nafrialdi Nafrialdi; Johannes Hudyono; Frans D Suyatna; Arini Setiawati (Acta Medica Indonesiana)
Background: the use of statin to lower blood cholesterol is often associated with bothersome adverse effects such as myopathy and liver dysfunction. NC120 is herbal lipid lowering drug containing red yeast rice (RYR) extract, guggulipid, and chromium picolinate, and expected to have better safety profile. The aim of this study was to evaluate the efficacy and safety profiles of NC120 in lowering blood lipid. Methods: this was a double blind randomized clinical trial comparing NC120 with placebo in subjects with hypercholesterolemia. Two capsules of NC120 or placebo were administered twice a day for 28 days. Blood total-cholesterol, LDL-cholesterol, and triglyceride were measured on day-0, day-7, and day-28. Unpaired t-test was used to compare study parameter between groups, and one-way ANOVA was used to compare within group. Results: 25 subjects received NC120 and 24 subjects received placebo. Significant decrease of total cholesterol and LDL-cholesterol were observed since day-7 in NC120 group, while the changes in placebo group were not significant at all time of observation. No significant decrease of triglyceride was observed in NC120 group and in placebo group. Side effects were minor and comparable between the two groups. Conclusion: NC120 is effective in reducing total cholesterol and LDL-cholesterol, but not triglyceride. This drug shows a good safety profile, and thus can be considered for patients who can not tolerate statin drugs.